A High-Throughput Screening System for Populus Wood-Associated Transcription Factors and Its Application to Lignin Regulation - Zhuang, Yamei; Chen, Sihui; Lian, Wenjun; Xu, Li; Wang, Dian; Wang, Congpeng; Meng, Jie; Tang, Xianfeng; Xu, Hua; Wang, Shumin; Du, Lin; Zhang, Yang; et al. (Frontiers in Plant Science, 2022)
Wood formation is involved in the interactions with specific DNA sequences and other regulatory proteins. To detect such interactions in wood development, we developed a high-throughput screening system with 517 Gal4-AD-wood-associated transcription factors (TFs) library from Populus alba × P. glandulosa cv ‘84K’. This system can be used for screening the upstream regulators and interacting proteins of targets by mating-based yeast-one hybrid (Y1H) and yeast-two-hybrid (Y2H) method, respectively. Multiple regulatory modules of lignin biosynthesis were identified based on this Populus system. Five TFs interacted with the 500-bp promoter fragment of PHENYLALANINE AMMONIA-LYASE 2 (PAL2), the first rate-limiting enzyme gene in the lignin biosynthesis pathway, and ten TFs interacted with PaMYB4/LTF1, a key regulator of lignin biosynthesis. Some of these interactions were further validated by EMSA and BiFC assays. The TF-PaPAL2 promoter interaction and TF-PaMYB4 interaction revealed a complex mechanism governing the regulation of lignin synthesis in wood cells. Our high-throughput Y1H/Y2H screening system may be an efficient tool for studying regulatory network of wood formation in tree species.